Weyl semimetals in models for ultracold atoms - Hansen, Andreas (UCPH NanoScience - a student research journal, 2018)
I study the effect of a non-Abelian gauge potential on a Weyl semimetal phase appearing in a particular 3D tight-binding model of fermions. The lattice I consider is characterized by a C3 rotational symmetry and by staggered π/2 magnetic fluxes on the triangular plaquettes in its horizontal planes. The energy spectrum is characterized by both single Weyl points with linear energy dispersions in all three momenta directions, and double Weyl points with quadratic energy dispersions in two directions and linear dispersion along the axis of the rotational symmetry.